2023
DOI: 10.1111/soc4.13139
|View full text |Cite
|
Sign up to set email alerts
|

Queering reproductive justice: Framing reproduction of gay men from a transnational perspective—Taiwan as a case

Jung Chen

Abstract: This article uses Taiwan as an example to argue that reproductive justice for gay men should be conceptualised within social, legal, and political contexts. Taiwan is the first Asian country to legalise same‐sex marriage, yet the law favours heterosexual couples and denies LGBTQ+ reproductive rights. Thus, Taiwanese gay men seek third‐party reproduction overseas to become parents. This article exemplifies gay men's unequal conditions from a non‐Western perspective. I re‐examine scholarly literature on the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Scholarly literature on reproductive governance in Taiwan indicated that due to legal exclusions, LGBTQ+ people sought assisted reproductive technologies (ARTs) as ‘a remedy for social infertility and justice’ (Wu, 2023, p. 149). With the increasing cross‐border reproductive care (CBRC), gay men from Taiwan and many other countries where ARTs and surrogacy are not accessible have been seeking transnational third‐party reproduction as a proactive action against reproductive injustice since they are forced into reproductive exile (Chen, 2023a; Inhorn & Patrizio, 2012; Smietana et al., 2018). A few countries provide altruistic surrogacy, such as Australia, Canada, New Zealand and the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly literature on reproductive governance in Taiwan indicated that due to legal exclusions, LGBTQ+ people sought assisted reproductive technologies (ARTs) as ‘a remedy for social infertility and justice’ (Wu, 2023, p. 149). With the increasing cross‐border reproductive care (CBRC), gay men from Taiwan and many other countries where ARTs and surrogacy are not accessible have been seeking transnational third‐party reproduction as a proactive action against reproductive injustice since they are forced into reproductive exile (Chen, 2023a; Inhorn & Patrizio, 2012; Smietana et al., 2018). A few countries provide altruistic surrogacy, such as Australia, Canada, New Zealand and the UK.…”
Section: Introductionmentioning
confidence: 99%